2001
DOI: 10.1094/pdis.2001.85.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness to Pumpkin Cultivars of Isolates of Phytophthora capsici from Pumpkin and Pepper

Abstract: Nine isolates of Phytophthora capsici obtained from pumpkin and pepper in diverse geographic areas, including Korea, France, Italy, and the United States, were evaluated for their ability to cause disease on nine Korean and Japanese pumpkin cultivars under controlled environmental conditions. No hypersensitive type of resistance was observed in any of the pumpkin cultivars inoculated with P. capsici. Disease incidence ranged from low to high, indicating varying levels of partial (quantitative) resistance. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 11 publications
2
28
1
2
Order By: Relevance
“…Phytophthora blight of pepper (Capsicum annum L.) caused by the oomycete plant pathogen Phytophthora capsici is one of the most destructive diseases all over the world (Hwang and Kim, 1995;Ristaino and Johnston, 1999;Lee et al, 2001;Hausbeck and Lamour, 2004). P. capsici attacks the roots, stems, leaves, and fruits of the pepper plant.…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora blight of pepper (Capsicum annum L.) caused by the oomycete plant pathogen Phytophthora capsici is one of the most destructive diseases all over the world (Hwang and Kim, 1995;Ristaino and Johnston, 1999;Lee et al, 2001;Hausbeck and Lamour, 2004). P. capsici attacks the roots, stems, leaves, and fruits of the pepper plant.…”
Section: Introductionmentioning
confidence: 99%
“…Gevens et al 2006 developed a detached fruit assay to survey the susceptibility of 480 cucumber cultigens and found that while no cultigens displayed a complete absence of infection, some did show a reduced level of sporulation, supporting the concept of quantitative resistance. Lee et al 2001 also observed quantitative resistance to nine isolates of P. capsici when tested on a wide range of pumpkin cultivars from Korea and Japan. In cucumber and other cucurbits, Ando et al 2009 demonstrated that the age of the fruit has a role in determining its susceptibility to P. capsici, with younger fruits, especially cucumbers, being the most susceptible until they reach full fruit length at about 10-12 days after pollination.…”
Section: Resistance To P Capsicimentioning
confidence: 79%
“…identified 3 dominant alleles through classical breeding that were found to be involved in conferring resistance to P. capsici as observed by an absence of the crown rot syndrome. In other cucurbits, including cucumber, quantitative, but not qualitative resistance has been observed (Ando et al 2009;Gevens et al 2006;Lee et al 2001). Gevens et al 2006 developed a detached fruit assay to survey the susceptibility of 480 cucumber cultigens and found that while no cultigens displayed a complete absence of infection, some did show a reduced level of sporulation, supporting the concept of quantitative resistance.…”
Section: Resistance To P Capsicimentioning
confidence: 97%
“…Lee et al (2001) juga mendapatkan adanya interaksi yang nyata antara geografi asal isolat P. capsici dari Capsicum dan labu dengan varietas labu yang diuji, dan ada kecenderungan kekhususan inang di dalam P. capsici yang diuji. Pada P. cactorum dari strawberi, analisis random amplified microsatellite (RAMS) menunjukkan isolat P. cactorum sebagai penyebab busuk buah dan busuk akar strawberi secara genetik berbeda, dan uji patogenisitas mengindikasikan kedua grup P. cactorum tersebut cenderung mempunyai kekhususan inang (Hantula et al, 2000).…”
Section: Hasil Dan Pembahasanunclassified